2011
DOI: 10.1007/s00592-011-0357-y
|View full text |Cite
|
Sign up to set email alerts
|

Prospective, randomized trial on intensive SMBG management added value in non-insulin-treated T2DM patients (PRISMA): a study to determine the effect of a structured SMBG intervention

Abstract: Self-monitoring of blood glucose (SMBG) is a core component of diabetes management. However, the International Diabetes Federation recommends that SMBG be performed in a structured manner and that the data are accurately interpreted and used to take appropriate therapeutic actions. We designed a study to evaluate the impact of structured SMBG on glycemic control in non-insulin-treated type 2 diabetes (T2DM) patients. The Prospective, Randomized Trial on Intensive SMBG Management Added Value in Non-insulin-Trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 49 publications
1
24
0
2
Order By: Relevance
“…Several recent trials of structured BGM included specific instructions on testing frequency and timing, interpreting and communicating these results, and integrating results into self-management plans. These studies have shown improved glycemic control in patients with T2DM who do not receive insulin therapy (8,9,97,98).…”
Section: T2dm Adult Patients With T2dmmentioning
confidence: 99%
“…Several recent trials of structured BGM included specific instructions on testing frequency and timing, interpreting and communicating these results, and integrating results into self-management plans. These studies have shown improved glycemic control in patients with T2DM who do not receive insulin therapy (8,9,97,98).…”
Section: T2dm Adult Patients With T2dmmentioning
confidence: 99%
“…The active control group received discretionary, unstructured SMBG, comprehensive patient education, and treatment adjustment according to HbA1c levels and hypoglycemia. 48 Publication of the PRISMA results is expected shortly, yielding further evidence regarding the effects of structured SMBG, including changes in patient and physician attitudes and behaviors. 48 …”
Section: Delivering Early Care In Diabetes Evaluation Studymentioning
confidence: 99%
“…48 Publication of the PRISMA results is expected shortly, yielding further evidence regarding the effects of structured SMBG, including changes in patient and physician attitudes and behaviors. 48 …”
Section: Delivering Early Care In Diabetes Evaluation Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Self-monitoring of seven-points on an SMBG device for 3 consecutive days once every three months in addition to daily tests resulted in better glycemic control compared to the active control group (Polonsky et al, 2011). Structured testing is a new method of less-frequent SMBG that guides glycemic management strategies and has the potential to improve problem-solving and decision-making skills for both patients and clinicians (Fisher et al, 2012;Scavini et al, 2013). Evidence suggests that less frequent SMBG can have favorable effects on glycemic control when both healthcare providers and patients appreciate the purpose of their SMBG measurements.…”
Section: Introductionmentioning
confidence: 99%